2019
DOI: 10.2147/ott.s221620
|View full text |Cite
|
Sign up to set email alerts
|

<p>Long Non-Coding RNA CDKN2B-AS1 Facilitates Laryngeal Squamous Cell Cancer Through Regulating miR-497/CDK6 Pathway</p>

Abstract: Background: CDKN2B antisense RNA 1 (CDKN2B-AS1), a long noncoding RNA, was reported to play crucial roles in the progression of multiple cancers. However, the functional roles and regulatory mechanism of CDKN2B-AS1 in human laryngeal squamous cell cancer (LSCC) remain unclear. The goals of this study were to investigate biological roles and underlying mechanisms of CDKN2B-AS1 in LSCC. Methods: The expressions of CDKN2B-AS1, miR-497 and cyclin-dependent kinase 6 (CDK6) were detected in LSCC tissues and cell lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 34 publications
2
19
0
Order By: Relevance
“…CDKN2B-AS1 , also known as ANRIL , is located at chromosome 9p21. CDKN2B-AS1 is reported to be upregulated in tumor tissues and function as an oncogenic lncRNA in pancreatic, ovarian and laryngeal squamous cell carcinoma 36 38 . Human miR-141 is located at chromosome 12p13.31 and is transcribed from a miR-200 family cluster.…”
Section: Discussionmentioning
confidence: 99%
“…CDKN2B-AS1 , also known as ANRIL , is located at chromosome 9p21. CDKN2B-AS1 is reported to be upregulated in tumor tissues and function as an oncogenic lncRNA in pancreatic, ovarian and laryngeal squamous cell carcinoma 36 38 . Human miR-141 is located at chromosome 12p13.31 and is transcribed from a miR-200 family cluster.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the expression of this lncRNA is upregulated in tumor tissues and plays a carcinogenic role. A previous study has reported that CDKN2B-AS1 acts as an oncogene in the tumorigenesis of laryngeal squamous cell carcinoma by regulating the miR-497/cyclin-dependent kinase 6 axis ( 96 ).…”
Section: Regulation Of Mir-497 Expressionmentioning
confidence: 99%
“…lncRNA CDKN2B antisense RNA 1 (CDKN2B-AS1), which is an antisense of the cyclin-dependent kinase inhibitor 2B (CDKN2B), plays important roles in various diseases including in cancers [15][16][17][18] . Zhu et al reported that interference of CDKN2B-AS1 restrains the metastasis and promotes apoptosis and senescence of cervical cancer cells via regulating miR-181a-5p/TGFβI axis.…”
Section: Introductionmentioning
confidence: 99%